Living Utopia? : Stories from Rojava - Wimmer, Christopher, (Social Sciences E-Books Online, Collection 2026., 2026)
For social movements around the world, Rojava embodies the real possibility of a better society: the revolution began there in 2012. In the Kurdish-dominated regions, an autonomous self-administration has been established based on the values of grassroots democracy, gender equality and ecology. The "Democratic Autonomous Administration of North and East Syria" now controls about a third of Syria's territory. It unites different ethnicities, religions and languages under its umbrella. A decade later, Christopher Wimmer examines the aspirations and reality of the "revolutionary society" from a critical perspective. Based on numerous interviews with people from all sectors of society - administration, education, military, medicine, etc. - in a mixture of reportage and analysis, he creates a polyphonic picture of the everyday life, hopes, and problems of the people on the ground.